2003
DOI: 10.1086/344772
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Nasal Carriage of Mupirocin‐Resistant, Methicillin‐ResistantStaphylococcus aureus(MRSA) in a Pet Dog Associated with MRSA Infection in Household Contacts

Abstract: Recurrent methicillin-resistant Staphylococcus aureus (MRSA) infection in a patient with diabetes and in his wife is described. Culture of nares samples from the family dog grew mupirocin-resistant (minimum inhibitory concentration >1024 microg/mL) MRSA that had a pulsed-field gel electrophoresis chromosomal pattern identical to the MRSA isolated from the patient's nares and his wife's wound. Further recurrence of MRSA infection and nasal colonization in the couple was prevented only after successful eradicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
0
9

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(169 citation statements)
references
References 14 publications
6
154
0
9
Order By: Relevance
“…Eight of the 10 case studies suggest that dogs can be vectors for MRSA bacteria (Cefai et al 1994, Manian 2003 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight of the 10 case studies suggest that dogs can be vectors for MRSA bacteria (Cefai et al 1994, Manian 2003 …”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this include the relative difficulty of swabbing cats for data collection or the fact that dogs tend to experience closer human contact. Four of the eight case reports noted that infection of human subjects persisted until the pet (as well as any other colonized or infected cohabitants) was treated with antimicrobials to which the bacteria were susceptible (Manian 2003, van Duijkeren et al 2004, Sing et al 2008). These observations are consistent with the common view that pets can serve as reservoirs of MRSA infection (Oehler et al 2009, Stein 2009, Gaze et al 2008, Morgan 2008, potentially causing re-infection of their owners after the owners have been treated for the initial MRSA infection.…”
Section: Bramble Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported isolation of MRSA from infected dogs [34,35], and case studies have shown that dogs of both infected patients and colonized subjects may be colonized with MRSA [10][11][12][13]. MRSA colonization has also been reported in healthy dogs belonging to healthy MRSA-negative members of veterinary clinic staff [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although case reports of human infection or colonization from companion animals [10][11][12][13][14] have shown the potential of animals to act as reservoirs for transmission of MRSA [15], there appear to be no published reports on the prevalence of carriage of S. aureus in owners and their dogs. Reported rates of canine carriage vary widely, but higher levels reported in early studies may be due to the inability to distinguish between S. aureus and S. intermedius, the staphylococcal species most frequently isolated from dogs [15,16].…”
Section: Introductionmentioning
confidence: 99%